THE DETERMINANTS OF EMPLOYEE'S PERFORMANCE: LEADERSHIP STYLE, ORGANIZATIONAL CULTURE AND JOB SATISFACTION (LITERATURE REVIEW) - Prima Sari Pascariati; Nandan lima Krisna (Dinasti International Journal of Education Management And Social Science, 2021)
This piece of research highlights a contextual understanding of employee performance’s concept by identifying factors affecting employee performance in the organization. The method of writing scientific articles is to use qualitative methods and library research. The results of this literature review article are: Leadership Style has a positive and significant effect on employee performance, Organizational Culture has a positive and significant effect on employee performance, and Job Satisfaction has a positive and significant effect on employee performance. On the other hand, the correlation between these factors has a vital role in maintaining employee’s performance and attitude.